2010
DOI: 10.1093/mp/ssp117
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoprotection by Protein-Bound vs Free Xanthophyll Pools: A Comparative Analysis of Chlorophyll b and Xanthophyll Biosynthesis Mutants

Abstract: When light absorbed by plants exceeds the capacity of photosynthesis, the xanthophyll violaxanthin is reversibly de-epoxidized to zeaxanthin in the so-called xanthophyll cycle. Zeaxanthin plays a key role in the protection of photosynthetic organisms against excess light, by promoting rapidly reversible (qE) and long-term (qI) quenching of excited chlorophylls, and preventing lipid oxidation. The photoprotective role of zeaxanthin, either free or bound to light-harvesting complexes (Lhcs), has been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 79 publications
10
133
0
Order By: Relevance
“…Similar results were obtained upon removal of both Lhcb4 and Lhcb6 ( figure 3d and table 2), thus ruling out the possibility that minor antennae modulate qM amplitude and kinetics. These data are consistent with the behaviour of npq4ch1 that lacks Chlb, and is thus devoid of all LHCs [37,38]; the slow phase of NPQ relaxation was found to be independent of LHC composition, indeed qM amplitude was similar in npq4 and npq4ch1 mutants ( figure 3e and table 2). State transitions lead to quenching of LHCII fluorescence by PSI [39] upon phosphorylation of LHCII, by STN7 kinase, driving its migration from PSII to PSI [40]; by using the mutant npq4stn7, we checked the possibility that state transition were involved in qM.…”
Section: (C) Role Of Xanthophyll Compositionsupporting
confidence: 85%
“…Similar results were obtained upon removal of both Lhcb4 and Lhcb6 ( figure 3d and table 2), thus ruling out the possibility that minor antennae modulate qM amplitude and kinetics. These data are consistent with the behaviour of npq4ch1 that lacks Chlb, and is thus devoid of all LHCs [37,38]; the slow phase of NPQ relaxation was found to be independent of LHC composition, indeed qM amplitude was similar in npq4 and npq4ch1 mutants ( figure 3e and table 2). State transitions lead to quenching of LHCII fluorescence by PSI [39] upon phosphorylation of LHCII, by STN7 kinase, driving its migration from PSII to PSI [40]; by using the mutant npq4stn7, we checked the possibility that state transition were involved in qM.…”
Section: (C) Role Of Xanthophyll Compositionsupporting
confidence: 85%
“…The same level of deepoxidation upon exposure to excess light and zeaxanthin binding to pigment-proteins, as assessed by Suc gradient fractionation and HPLC analysis, was found in wildtype and lhcsr psbs KO plants, as shown by a deepoxidation index of 0.76 in both cases. We observed that the exchange of violaxanthin versus zeaxanthin is rapid and more complete on LHC binding sites with respect to previous reports on Arabidopsis, which has a deepoxidation index of 0.50 (Dall'Osto et al, 2010). When comparing the zeaxanthin distribution pattern from wild-type excess light-treated samples, we observed an enrichment in fractions 23 to 27 of the Suc gradient ( Figure 6B).…”
Section: Zeaxanthin Binds To Lhcsr In P Patenssupporting
confidence: 71%
“…Previous work on C. reinhardtii (Baroli et al, 2003) and Arabidopsis (Havaux and Niyogi, 1999) showed an enhanced ROS scavenging activity of zeaxanthin with respect to preexisting violaxanthin both in the lipid phase (Havaux et al, 2007) and bound to pigment-proteins (Dall'Osto et al, 2010). Recent work has shown a photoprotective ROS-scavenging activity of zeaxanthin under salt and osmotic stress resistance in P. patens (Azzabi et al, 2012).…”
Section: Other Photoprotective Activities Of Zeaxanthin Besides Quencmentioning
confidence: 96%
See 1 more Smart Citation
“…Here they absorb light across a broader range of the spectral region in which the sun irradiates maximally and transfer the energy to chlorophyll, initiating the photochemical events of photosynthesis (Polívka and Frank 2010). In plants, carotenoids are bound in discrete pigment-protein complexes referred to as the LHCII trimeric complex, which typically benefits from lutein, neoxanthin, as well as violaxanthin to transfer energy to chlorophyll (Pogson et al 2005;DemmigAdams and Adams 2006;Dall'Osto et al 2010). A curious marine dinoflagellate, Amphidinium carterae alternatively evolved a peridinin-chlorophyll protein complex that contains more of the bound carotenoid (peridinin) when compared with chlorophyll (Hofmann et al 1996;Polívka and Frank 2010) (Fig.…”
Section: Photosynthesis and Photoprotection In Plantsmentioning
confidence: 99%